Marley & me. The puppy years The puppy years - Regency Enterprises; Damian, Janeen, 1961-; Damian, Michael; Dolphin, Connie; Zahara, Alex.; Russell, Grayson; Turner, Travis; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2011)
Marley is back for more tail-wagging fun, and this time he speaks! That's right, the world's worst dog has a frisky voice and an attitude to match. Join Marley for his mischievous puppy years as he and his summer pal, Bodi Grogan, wreak havoc on a neighborhood dog contest. Marley outwits dobermans, shepherds, and collies, while stealing hearts in his own unique and lovable way. Fetch big laughs for the whole family!
Special features: Marley & me: the puppy years goes to training camp; part of the family; my favorite moments.
Alex Zahara, Grayson Russell, Travis Turner.
Rating: PG; for some mild rude humor CHV rating: G.
DVD, region 1; widescreen 1.78:1; dual layer; Dolby Digital 5.1, NTSC.
English dialogue; French or Spanish subtitles; Closed-captioned; Subtitled for the deaf and hard of hearing.
Keywords: Labrador retriever -- Drama; Dogs -- Training -- Drama; Perros -- Adiestramiento -- Teatro; Feature films; Children's films; Video recordings for the hearing impaired